Comparing Proxy, Adolescent, and Adult Assessments of Functional Ability in Adolescents With Juvenile Idiopathic Arthritis. Issue 4 (27th March 2020) - Shoop‐Worrall, Stephanie J. W.; Hyrich, Kimme L.; Verstappen, Suzanne M. M.; Sergeant, Jamie C.; Baildam, Eileen; Chieng, Alice; Davidson, Joyce; Foster, Helen; Ioannou, Yiannis; McErlane, Flora; Wedderburn, Lucy R.; Thomson, Wendy; et al.
Abstract : Objective: In pediatric research, investigators rely on proxy reports of outcome, such as the proxy‐completed Childhood Health Assessment Questionnaire (C‐HAQ), to assess function in juvenile idiopathic arthritis (JIA). As children mature, they may self‐complete the adult HAQ or the unvalidated adolescent‐specific C‐HAQ. It is unclear how these measures compare and whether they are directly interchangeable. The present study was undertaken to compare agreement between the proxy‐completed C‐HAQ, adolescent‐specific C‐HAQ, and the HAQ at initial presentation to pediatric rheumatologic care and 1 year following the first presentation in adolescents with JIA. Methods: Adolescents ages 11–17 years participating in the Childhood Arthritis Prospective Study (CAPS), a UK multicenter inception cohort, were included. In a CAPS substudy, adolescents self‐completed the adolescent‐specific C‐HAQ and the HAQ, and proxies simultaneously completed the proxy‐completed C‐HAQ at baseline and 1 year. Correlation and agreement between scores were assessed at baseline. Agreement and ability to similarly classify clinically important changes over time were assessed at 1 year following initial presentation to rheumatologic care. Results: A total of 107 adolescents (adolescent‐specific C‐HAQ and HAQ) or their proxies (proxy‐completed C‐HAQ) had completed all 3 measures at baseline. Median age at diagnosis was 13 years, and 61% were female. Although the 3 scores demonstrated strong correlations (r > 0.8), they were not completely interchangeable, with agreement ranging between 70% and 80%. There was similar agreement between the changes in scores between baseline and 1 year. Using proxy‐completed C‐HAQ minimum clinically important cutoffs, the adolescent‐specific C‐HAQ and the HAQ similarly classified 80% to 90% of adolescents as having improved or worsened. Conclusion: While there is relatively high agreement and similar classification of change between HAQ and the 2 C‐HAQ scores, these are not completely interchangeable. This impacts the comparison of function when measured in different ways over the lifespan.